A low-cost toolbox for high-resolution vulnerability and hazard-perception mapping in view of tsunami risk mitigation: Application to New Caledonia. (August 2021) - Thomas, Bruce E.O.; Roger, Jean; Gunnell, Yanni; Sabinot, Catherine; Aucan, Jérôme
Abstract: The drive towards improving tsunami risk mitigation has intensified along many populated coastlines. Like many islands in the Pacific Ocean, the coastal population of New Caledonia is exposed to tsunamis triggered by powerful earthquakes. Intersecting exhaustive population data with high-resolution building location data within a user-defined coastal fringe is an accurate means of geolocating vulnerable residents, and an important step towards disaster risk reduction. This paper presents a mixed methodology built on GIS-based dasymetric techniques for assessing, classifying, and mapping population distribution in New Caledonia, with the aim of quantifying and ranking the areas most vulnerable to tsunami-related hazards. Results reveal that 33% of the population, inclusive of previously unmapped precarious housing, lives between sea level and the 10 m elevation contour in well-defined clusters. A pilot field survey of 412 respondents was additionally conducted in the capital Nouméa (66% of the nation's population) to assess tsunami awareness, risk perception, and risk-related behavioral patterns among the ethnically and demographically diverse population. By further mapping the spatial association between coastal population concentrations, the perceived natural shielding capacities of coral reefs and mangroves, and the benefits of alarm siren networks, the study delivers a comprehensive assessment of the country's disaster preparedness, with policy recommendations for the future. The methodology is transferable to other types of hazards and other insular settings where civil security and risk-management organizations acquire and curate reliable primary data but may also need guidelines for transforming them into serviceable disaster risk reduction methods and policies. Highlights: The population of New Caledonia (Western Pacific) is vulnerable to tsunami hazards. A GIS-based mapping methodology and atlas of exposure to tsunami risk are presented. A perception survey was conducted to assess risk awareness based on age and ethnicity. Some mitigation options (reefs, mangroves, education, warning systems) are discussed. The methodological package is transferable to other disaster risk reduction contexts.